2018
DOI: 10.1080/00071668.2018.1521511
|View full text |Cite
|
Sign up to set email alerts
|

Feeding broilers with thyme essential oil loaded in chitosan nanoparticles: an efficient strategy for successful delivery

Abstract: 1. The use of chitosan nanoparticles (CNPs) for the entrapment of active components has gained considerable interest in food and pharmaceutical industries due to its mucous adhesiveness, non-toxicity, biocompatibility and biodegradability. 2. This study aimed to investigate the usefulness of feeding encapsulated thyme essential oil (E-TEO) on performance, blood parameters, immunity and ileal microflora in broilers. 3. CNPs were prepared by using ionotropic gelation and structurally characterised by dynamic lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
2
25
0
1
Order By: Relevance
“…Several biopolymeric matrices viz. chitosan, dextran, starch, cellulose, and alginate have been used as a carrier agent for the encapsulation of EO owing to their biodegradable, biocompatible, and non-toxic nature (Hosseini and Meimandipour, 2018). Therefore, encapsulated EOs could be the best non-toxic and eco-friendly alternatives of synthetic preservatives for practical application in the field of agriculture and the food sector.…”
Section: Introductionmentioning
confidence: 99%
“…Several biopolymeric matrices viz. chitosan, dextran, starch, cellulose, and alginate have been used as a carrier agent for the encapsulation of EO owing to their biodegradable, biocompatible, and non-toxic nature (Hosseini and Meimandipour, 2018). Therefore, encapsulated EOs could be the best non-toxic and eco-friendly alternatives of synthetic preservatives for practical application in the field of agriculture and the food sector.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous mixtures of medicinal plants which are commercially available for the poultry industry claim to have bio-functional advantages regarding growth performance and immunocompetence. The results of recent research have shown that plant essential oils can be produced and added to the diet using micro and nanoencapsulation technologies at low and economic levels in order to allow slow release upon ingestion and have a direct effect on the target tissues (e.g., intestine) (Hosseini & Meimandipour, 2018;Amiri et al, 2020;Lee et al, 2020). Despite examining the effects of some of these products individually, there is no enough data to compare the effects of these new (micro or nano encapsulated) forms with common forms of herbal additives.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Hosseini and Meimandipour ( 2018 ), a total of 250 one‐day‐old male Ross 308 chickens for fattening were allocated to five dietary treatments and distributed in five pens per treatment, in groups of ten birds per each pen. Two basal diets based on maize and soybean meal (starter 1−21 days and grower 22−42 days) were either not supplemented (control) or supplemented with different treatments.…”
Section: Assessmentmentioning
confidence: 99%
“…( 2019a , 2020 ), 50 mg chlortetracycline/kg feed; Begin ( 1971 ), 50, 100 and 200 mg chlortetracycline/kg feed; Stutz and Lawton ( 1984 ), 55 mg chlortetracycline/kg feed; Han et al. ( 2012 ), Hosseini and Meimandipour ( 2018 ) and Li et al. ( 2007 ), 80 mg chlortetracycline/kg feed from day 1 to day 21 of age and then 50 mg chlortetracycline/kg feed from day 22 to day 42 of age; Alvares et al.…”
Section: Assessmentmentioning
confidence: 99%